376 Ancient grains as a novel dietary fiber and carbohydrate source in canine diets. (7th December 2018) - Traughber, Z; He, F; Mangian, H; Hoke, J; Davenport, G; de Godoy, M
Abstract: Ancient grains are becoming increasingly popular in both the human and petfood markets today and show potential as novel fiber and carbohydrate sources. Current data suggests lower glycemic responses through their dietary inclusion as well. Thus, the objective of this study was to evaluate the use of ancient grains in canine diets and their effect on glucose utilization. Five diets were formulated with either amaranth (AM), millet white proso (MWP), quinoa (QU), or oat groats (OG), with the last diet formulated with rice (CON) as the main ingredient source. Ten adult female beagles (mean age = 4.2 ± 1.14 yr; mean BW = 11.1 kg ± 1.17 kg) were used in a replicated 5x5 Latin square design. Each period consisted of 15 d, with 10 d of diet adaptation followed by 4 d of total fecal and urine collections and one day allocated for evaluating glycemic responses. A baseline blood sample was also analyzed for serum chemistry and complete blood counts. Food was offered twice daily and fed to maintain body weight. Fecal score was evaluated on a 5-point scale and was higher (P < 0.05) in dogs fed QU (3.0) in contrast to CON (2.7), but did not differ in all other diets. Apparent total tract (ATT) dry matter digestibility was higher (P < 0.05) in MWP compared to CON, AM, and OG. ATT crude protein digestibility was lower (P < 0.05) in QU compared to CON and MWP, with no differences between all other diets. OG had a lower (P < 0.05) average glycemic response than both AM and QU with no differences seen between all other diets. In conclusion, ancient grains show similar AAT macronutrient digestibility to a rice-based diet as well as potential in lowering glycemic responses when utilized as the main carbohydrate source in canine diets.